Self-Harm Behavior Among Medical Profession Students at YARSI University and its Review from an Islamic Perspective - Animas Arum Kholifah Hartono; Citra Fitri Agustina; Karimulloh Karimulloh; Miranti Pusparini (Eduvest - Journal of Universal Studies, 2026)
Self harm behavior is a deliberate act of injuring oneself without suicidal intent, often emerging as a response to emotional distress. Medical clerkship students are vulnerable to such behavior due to academic pressure, clinical responsibilities, and psychological stress, which can affect both mental health and academic performance. This research aims to describe the level of self harm tendency, its psychological and academic impacts, and to examine this behavior from an Islamic perspective among medical clerkship students at YARSI University. This research employed a descriptive quantitative design with a cross-sectional approach involving 96 medical clerkship students. Data were collected using the 22-item Self-Harm Inventory (SHI) questionnaire and analyzed descriptively using IBM SPSS Statistics version 26. The mean SHI score was 28.99, with most respondents categorized as having a low self-harm tendency (85.4%), followed by moderate (13.5%) and high (1%) tendencies. The majority also exhibited low levels of psychological and academic impact, although a small proportion experienced emotional instability and decreased learning motivation. Overall, most students demonstrated a low tendency toward self-harm, yet those with moderate to high scores require particular attention. In Islam, self harm is prohibited as it contradicts the principle of ḥifẓ al-nafs (protection of life). It is recommended that universities provide accessible counseling services, mental health support, and spiritual guidance programs as preventive and promotive measures to help students manage academic and emotional stress more adaptively.